Aspectos históricos da creche pública em Sorocaba a partir das memórias de seus protagonistas - Aceituno, Gabriela (Universidade Federal de São Carlos, 2017)
This paper rescues the historical context of the beginning of child care in Sorocaba and analyzes the process of institutionalization of day care. The research, in its methodological organization, is qualitative and bibliographical, and was carried out from the reading of theses, articles, books and documents referring to the history of day care in the country, with attention to the process in Sorocaba, including federal laws, state and municipal education and childhood. In addition, reinforcing the qualitative aspect, the research was also based on interviews carried out in June and July 2017, with people who worked at the beginning of the day care center in the city, or even before their institutionalization, and who participated directly in the process of inclusion of the nursery in the field of Education immediately after the Federal Constitution, and in the Sorocaba Secretariat of Education in the year 2016. Thus, it is a descriptive bibliographical research, supported by the Oral History methodology. With the main objective of mapping the history of child care in Sorocaba and, secondarily, pointing out and reflecting on the conventions we have about child care. The bibliographical research and the interviews conducted allow us to identify advances achieved by the day care center over the years and the challenges to be faced today.
Historical aspects of the public nursery in Sorocaba from of the memories of its protagonists
Keywords: Educação infantil; História da Creche; Sorocaba; Child education; Childhood History; Sorocaba (city); CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO